A study of the information needs and uses of the students, faculty and research staff of the College of Forestry, University of the Philippines at Los Banos - Belen, Flor E.; Sison, Josephine C.; De la Cruz, Reynaldo E. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1984)
This study is an attempt at identifying the information needs and uses of the students, faculty, and research staff of the College of Forestry, University of the Philippines at Los Banos, as well as assessing the use made of the College of Forestry Library Resources and Information Services.
The study made use of the descriptive survey method of research, with a questionnaire as a data gathering tool.
The data indicated that the respondents visited the library several times a week; that they sought information to acquire new ideas related to their work of field of interest; that their sources of information were friends and colleagues, and other libraries; that they were satisfied with their present method of obtaining information; and that they generally asked the assistance of the library staff in their literature search.
The UPLB College of Forestry Library was found to be not as effective as it should be in terms of meeting the information needs of its constituents.
Mimeographed.
Special Problem (Master of Library Science)--University of the Philippines Diliman
Keywords: Forests and forestry--Information services--Philippines--Use studies; University of the Philippines Los Banos. College of Forestry